2019
DOI: 10.1016/j.cub.2018.12.039
|View full text |Cite
|
Sign up to set email alerts
|

Deconstructing Theory-of-Mind Impairment in High-Functioning Adults with Autism

Abstract: Highlights d Novel task enables model-based analysis and decomposition of theory of mind (ToM) d Learning of intentions was impaired in high-functioning adults with autism (ASD) d ToM impairment in ASD was specific; belief tracking and ToM reasoning remained intact d Model parameters correlate with ASD symptom severity, pointing to new research targets

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 36 publications
3
22
0
1
Order By: Relevance
“…Yet they may have problems aligning (model-free) and selecting the correct response as well as problems incorporating and inferring the mental state of other people (model-based). Indeed, Rosenthal et al (2019) recently characterized specific impairments in model-based mentalizing among ASD participants, showing that ASD participants demonstrated specific impairments in using their estimates of agent belief to understand agent intentions.…”
Section: Out Of the Loop: Psychopathologies That Involve Impaired Adaptive Empathymentioning
confidence: 99%
“…Yet they may have problems aligning (model-free) and selecting the correct response as well as problems incorporating and inferring the mental state of other people (model-based). Indeed, Rosenthal et al (2019) recently characterized specific impairments in model-based mentalizing among ASD participants, showing that ASD participants demonstrated specific impairments in using their estimates of agent belief to understand agent intentions.…”
Section: Out Of the Loop: Psychopathologies That Involve Impaired Adaptive Empathymentioning
confidence: 99%
“…Recent evidence suggests that by disrupting activity in the brain's mentalizing network (C. A. Hill et al, 2017), as noted, or by studying a clinical population with disrupted mentalizing ability (Rosenthal et al, 2019), we can show that mentalizing is necessary for some particular social learning processes. However, this evidence is still extremely limited and preliminary, thus more studies are needed to generalize these finding to a range of observational learning and strategic social interaction tasks.…”
Section: Discussionmentioning
confidence: 93%
“…It is possible that additional dysfunctional features of network configurations across the whole brain (or whole hemisphere) that we missed in the present study could be revealed by using a task in the scanner directly involving a behavioral response from subjects. On the one hand, task-fMRI data can have the benefit of closely linking the brain with behavior [83]. On the other hand, passive viewing has the advantage of avoiding confounding activation differences that arise merely from different task performances.…”
Section: Discussionmentioning
confidence: 99%